Effect of nitrogen levels and liquid nano urea application on growth and yield of rice (Oryza sativa L.) - Kowsalya, Bassa Vasavi; Poonguzhalan, R; Saravanane, P; Nadaradjan, S (ORYZA-An International Journal of Rice, 2023)
A field experiment was conducted at Pandit Jawaharlal Nehru College of Agriculture and Research Institute, Karaikal to study the effect of nitrogen levels and liquid nano urea application on the growth and yield of rice (Oryza sativa L.) during samba 2021 (September 2021 to January 2022) under puddled transplanted condition, involving fourteen treatments in a randomized block design (RBD) replicated thrice.  The experiment involved a combination of four levels of nitrogen (0, 50, 75 and 100 % recommended dose of N) with three methods of liquid nano urea application (seed treatment, root dipping and foliar spraying) along with recommended dose of fertilizers and control.  The results revealed that the application of 75 % recommended N + seed treatment with liquid nano urea resulted in the highest values for plant height, leaf area index, leaf area duration, dry matter production and number of tillers hill-1 followed by application of 100 % recommended N + seed treatment with liquid nano urea.  Application of 75 % recommended N + seed treatment with liquid nano urea increased the grain yield by 14.8 and 84.3 % and straw yield by 6.5 and 76.4 % over recommended NPK and control, respectively.